PRAKTIK JUAL BELI BUAH PETAI DI POHON DENGAN SISTEM BORONGAN PERSPEKTIF FIKIH MUAMALAH - YUNIARTIK YUNIARTIK (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Selling and buying fruit with a wholesale system is one of the buying and selling practices that has existed for a long time. As is often done by the people in Ratu Sepudak, namely buying and selling petai fruit on trees with a wholesale system. The focus of this research is to find out how the practice of buying and selling petai fruit on trees with a muamalah fiqh perspective wholesale system in Ratu Sepudak Village, Galing District, Sambas Regency. The research method used is qualitative. Sources of data in the form of primary data and secondary data. Data collection techniques are interviews, observations, as well as from books and journals about buying and selling. The data processing technique used is descriptive analysis, namely reviewing the practice of buying and selling petai fruit on trees with a wholesale system in Ratu Sepudak Village using fiqh muamalah and then drawing conclusions. The results of this study are based on the perspective of muamalah fiqh, the practice of buying and selling petai fruit with a wholesale system in Ratu Sepudak Village is not valid because the quantity and quality of petai fruit is unknown, which means that this sale and purchase contains elements of gharar and includes buying and selling muhaqolah which is prohibited in Islam.